Proximal Fibular Osteotomy vs high Tibial Osteotomy in medial compartment Osteoarthritis of knee - Mahadik, Sujay K; Pandey, Shriansh; Belsare, Neel S; Shinde, Girish S; Deshpande, Shrikant B (Asian Journal of Medical Sciences, 2021)
Background: Osteoarthritis of knee is one of the common conditions seen in older individuals and known to affect quality of life considerably. It makes it difficult for individuals with knee osteoarthritis to climb stairs, walk long distances, and stand for long time and squatting. In intractable cases not responding to conservative management surgical management such as proximal fibular Osteotomy (PFO) or high tibial Osteotomy (HTO) is routinely done. We conducted this comparative study to analyse the functional outcome of patients who had undergone HTO and PFO for medial compartment osteoarthritis of knee joint. Aims and Objectives: 1) To analyse the functional outcome of patients who had undergone HTO and PFO for medial compartment osteoarthritis of knee joint. 2) To compare complication rates in both the groups. Materials and Methods: A total of 60 patients with medial compartment knee osteoarthritis were included in this study on the basis of a predefined inclusion and exclusion criteria. Patients were randomized to 2 groups. Thirty patients undergoing proximal fibular osteotomy (Group A) and 30 patients undergoing high tibial osteotomy (Group B). The patients were followed up for improvements in functional outcome for 12 months. The statistical analysis was done using SSPS 21.0 software and p value less than 0.05 were taken as statistically significant. Results: Mean time for surgery was less for PFO surgery as compared to HTO and the difference was statistically significant. Moreover mean bleeding amount, drainage volume and time required for full weight bearing was low in PFO group as compared to HTO group and the difference was found to be statistically significant (P<0.05). The mean VAS score at the time of presentation in PFO and HTO groups was found to be 4.9 +/- 1.12 and 4.7 +/- 1.02 respectively. A statistically significant reduction in pain was documented at the time of follow up of 4 weeks in both the groups. The functional outcome and complication rates were comparable in both the groups. Conclusion: Proximal fibular osteotomy is a better option as compared to high tibial osteotomy in terms of mean surgery time, mean bleeding amount, drainage volume and time required for full weight bearing. Functional outcome and improvement in VAS were comparable in both the groups.